Spillover of public opinion into EU harmonization on asylum policy : Evidence for Belgium, France and Germany - Abbaszada, Aygul (ADA University, 2019)
This thesis discusses how public opinion an influence on the administrative decision making procedures in Belgium, France and Germany in terms of recognition rates regarding applications for asylum, relocation rate and migrant integration rate and how varied public opinion in the Member States influences EU harmonization in asylum policy. Utilizing Most Similar System Design (MSSD) the research conducts an analysis to examine public opinion on asylum seekers and refugee policy in three different EU Member States (Belgium, France, Germany) and to identify how individual differences existing within each of these countries challenges implementation of Common European Asylum System (CEAS). The study found that although the European Union grows around normative values, the still strong nation-state reflexes cause difficulties in establishing common transnational migration policies.
Keywords: Public and International Affairs; Public opinion -- European Union.; European Union -- Asylum policy.